Nitrogen removal in freshwater sediments of riparian zone: N-loss pathways and environmental controls - Ye, Fei; Duan, Lei; Sun, Yaqiao; Yang, Fan; Liu, Rui; Gao, Fan; Wang, Yike; Xu, Yirong (Frontiers in Microbiology, 2023)
The riparian zone is an important location of nitrogen removal in the terrestrial and aquatic ecosystems. Many studies have focused on the nitrogen removal efficiency and one or two nitrogen removal processes in the riparian zone, and less attention has been paid to the interaction of different nitrogen transformation processes and the impact of in-situ environmental conditions. The molecular biotechnology, microcosm culture experiments and 15 N stable isotope tracing techniques were used in this research at the riparian zone in Weinan section of the Wei River, to reveal the nitrogen removal mechanism of riparian zone with multi-layer lithologic structure. The results showed that the nitrogen removal rate in the riparian zone was 4. 14-35.19μmolDenitrification, dissimilatory reduction to ammonium (DNRA) and anaerobic ammonium oxidation (anammox) jointly achieved the natural attenuation process of nitrogen in the riparian zone, and denitrification was the dominant process (accounting for 59.6 %). High dissolved organic nitrogen and nitrate ratio (DOC:NO3 -) would promote denitrification, but when the NO3 -content was less than 0.06 mg/kg, DNRA would occur in preference to denitrification. Furthermore, the abundances of functional genes (norB, nirS, nrfA) and anammox bacterial 16S rRNA gene showed similar distribution patterns with the corresponding nitrogen transformation rates. Sedimentary NOX -, Fe(II), dissolved organic carbon (DOC) and the nitrogen transformation functional microbial abundance were the main factors affecting nitrogen removal in the riparian zone. Fe (Ⅱ) promoted NO3 - attenuation through nitrate dependent ferrous oxidation process under microbial mediation, and DOC promotes NO3 -attenuation through enhancing DNRA effect. The results of this study can be used for the management of the riparian zone and the prevention and control of global nitrogen pollution.